Remote sensing of light pollution in Slovenia - Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2018)
The study deals with the problem of light pollution in Slovenia in the period 2013-2017. Remotely sensed data were obtained from the Suomi NPP satellite, which is scanning the earth's surface at night. The findings and geospatial trends of light pollution in the mentioned time period are discussed on the national and municipal levels. Some areas with very high and low levels of light pollution were exposed.